المواجهة الجنائية للرشوة في قانون النزاهة ومكافحة الفساد : دراسة تحليلية - المصاروة، سيف إبراهيم محمد; الكساسبة، عبدالرؤوف أحمد مفلح (الجامعة الأردنية - عمادة البحث العلمي, 2018)
لما تؤديه جريمة الرشوة من إخلالٍ بمبدأ المساواة بين المواطنين، وفقدان الثقة في دولة القانون -باعتبارها من أهم صور الفساد وأكثرها انتشارا- تأتي هذه الدراسة للوقوف على المواجهة الجنائية لجريمة الرشوة في قانون النزاهة ومكافحة الفساد الأردني رقم (13) لسنة 2016. فتناولنا السياسة التجريمية لمواجهة جريمة الرشوة في هذا القانون، حيث أحال المشرع إلى جريمة الرشوة التقليدية المنصوص عليها في قانون العقوبات، وجرائم الرشوة المستحدثة الواردة في الاتفاقيات الدولية التي صادق عليها الأردن، وما يؤديه هذا المنهج من إخلال بمبدأ الشرعية الجنائية، واثارة العديد من الإشكاليات الخاصة بتطبيق الاتفاقيات الدولية وتفسيرها، وما رأيناه من ضرورة دمج هذه الجرائم في قانون العقوبات، وعدم الاكتفاء بالإحالة إليها. كما تناولنا السياسة العقابية لهذا القانون في مواجهة جريمة الرشوة، حيث فرض المشرع عقوبة واحدة لكافة جرائم الرشوة المستحدثة، وكانت من البساطة التي لا تنسجم مع جسامة الجريمة، التي نرى تشديدها، بخلاف جريمة الرشوة التقليدية المتفاوتة بين جنائية وجنحية الوصف. وقد أنهينا الدراسة بخاتمة احتوت على النتائج والمقترحات.
Due to the undesired consequences of the crime of bribery regarding the breach of the principle of equality among citizens and their loss of confidence towards the state of law – considering it as one of the most important and most widespread corruption methods this study aims to identify the criminal confrontation of the crime of bribery in the Jordanian Honesty and Anti-Corruption Act Number 13 of (2016). I addressed the incriminating policy for the confrontation of the crime of bribery in this law, which referred us to the traditional crime of bribery stated in the Penal Code, as well as the new crimes of bribery stated in the international conventions approved by Jordan. I, also, addressed the negative consequences of this approach regarding the breach of the principle of criminal legitimacy, as well as the awaking of the several problematic issues which are related to the application of the international conventions and interpreting them, and the importance of including these crimes in the Penal Code. I, also, addressed the punitive policy of this law in confronting this crime, where the legislator has imposed one penalty for all the novel bribery crimes, which is characterized by simplicity that is not consistent with the gravity of the crime, which must be severe, other than the crime of traditional bribery varying in descriptions either as criminal or offensive. The study ends with a conclusion that includes the findings and the recommendations.
Keywords: الأردن -- القانون الجنائي -- قانون العقوبات -- مكافحة الفساد -- الرشوة